2006
DOI: 10.1111/j.1460-9568.2006.04963.x
|View full text |Cite
|
Sign up to set email alerts
|

Laminin and growth factor receptor activation stimulates differential growth responses in subpopulations of adult DRG neurons

Abstract: Neurons in the adult rat dorsal root ganglion (DRG) can be classified into at least three separate subpopulations based on morphologic and phenotypic differences. In this study we have focused on the growth response of these specific subpopulations in vitro with respect to laminin (LN) and growth factor receptor activation. Using a cell selection approach we show that LN-induced neurite growth occurs in the absence of added trophic factors only in heavy-chain neurofilament-positive and calcitonin gene-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 70 publications
4
55
0
Order By: Relevance
“…In contrast, the GDNF-responsive IB4 þve cells required an extra day in culture to generate a comparable number of neurite-bearing neurons. The slower extension of neurites by GDNF-responsive cells compared to NGF-responsive cells has been previously reported (Tucker et al, 2006;Leclere et al, 2007).…”
Section: Discussionsupporting
confidence: 54%
“…In contrast, the GDNF-responsive IB4 þve cells required an extra day in culture to generate a comparable number of neurite-bearing neurons. The slower extension of neurites by GDNF-responsive cells compared to NGF-responsive cells has been previously reported (Tucker et al, 2006;Leclere et al, 2007).…”
Section: Discussionsupporting
confidence: 54%
“…Boosting expression of a7 integrin in IB4-positive neurons by infection with the a7BX2 integrin subunit failed to enhance neurite outgrowth (Leclere et al, 2007). The mechanisms underlying regeneration of this IB4-positive population of neurons do appear to be intrinsically different, for example exogenous laminin induces neurite outgrowth in a concentration-dependent manner in NF200/CGRP-positive sensory neurons but not the IB4-positive cell population (Tucker et al, 2006).…”
Section: With Permission Copyright Elsevier (2007)mentioning
confidence: 97%
“…Direct knockdown of Akt via siRNA blocked neurite outgrowth in adult NGF-responsive DRG neurons, while inhibition of MEK/MAPK had no significant effect [35]. The same group previously reported that pharmacological inhibition of Akt with the phosphatidylinositol ether analog 1L6-hydroxymethyl-chiro-inositol-2-(R)-2-O-methyl-3-O-octadecyl-sn-glycerocarbonate (Akt inhibitor) or of PI3K with LY294002 attenuates neurite outgrowth, analysed in Snail neurons Positive: inhibition reduced neurite outgrowth [48] PC12 cells Positive: increases neurite outgrowth; elongation [40][41][42][43] Negative: inhibited neurite outgrowth; reduced branching [31,32,44,47] No significant effect [46] response to NGF, laminin or NGF plus laminin [36]. In the nervous system, activating transcription factor 3 (ATF3) is only expressed in injured neurons, and the co-overexpression of ATF3 and MEKK1 was shown induce neurite elongation via Akt activation in superior nerve ganglion neurons and in PC12 cells without NGF stimulation [37].…”
Section: Neurite Elongationmentioning
confidence: 99%